Myocysticercosis presenting as an uncommon cause of chest wall swelling: A case report - Das, Sunil Kumar; Pariyar, Bijaya (Journal of General Practice and Emergency Medicine of Nepal, 2023)
Cysticercosis is a common helminthic parasitic infection in humans caused by larva of Taenia solium. It most commonly affects the brain causing neurocysticercosis. It also affects the different system of the body as eyes, subcutaneous tissue, eye, lungs. Diagnosis of cysticercosis is usually done by imaging such as ultrasound for cutaneous, muscular and orbital infection whereas CT scan for the neuro cysticercosis. We report a case of myocysticercosis on lateral chest wall of the 7-year-old male from a rural region of Nepal.